Original article The consistency of Fletcher-Suit applicator geometry and of the rectal probe’s position in high dose rate brachytherapy treatment fraction of cervix carcinoma - Pálvölgyi, Jenő (Journal of Contemporary Brachytherapy, 2009)
Purpose: The dose values computed with the treatment planning system and the in vivo dose measurements with semiconductor detectors in rectum during the high dose rate brachytherapy treatment fraction of the cervix carcinoma are occasionally significantly different. We’ve investigated the consistency of the Fletcher-Suit applicator geometry and the in vivo rectal probe’s position stability during the high dose rate brachytherapy treatment fraction. Material and methods: The patient lied in a lithotomic position during a biplane reconstruction images, throughout the treatment planning and dose administration. We obtained post-treatment reconstruction images and prepared a post-treatment plan. The amount of 14 treatment fractions of 10 patients were considered in the study. Two methods were applied: evaluation of the difference of reconstructed pre-treatment and post-treatment applicator points and rectal probe’s detectors being relevant to the co-ordinate system fixed to the applicator, and estimation of applicators and rectal probe’s reallocation with respect to the pelvic bones with registration of pre- and post-treatment reconstruction images. Results: We’ve experienced good consistency in the Fletcher-Suit applicator geometry in all treatment fractions. 70% of them presented small variation in the rectal probe’s position, while the rest showed significant shift in the applicator or rectal probe’s position with regard to the pelvic bones.